2023
DOI: 10.3389/fneur.2023.1126652
|View full text |Cite
|
Sign up to set email alerts
|

Sudden unexpected death in epilepsy: Investigation of autopsy-based studies

Abstract: Epilepsy is a common neurological disorder that is associated with increased morbidity and mortality. Sudden unexpected death in epilepsy (SUDEP) is one of the most common causes for epilepsy-related deaths and its characteristics remain largely unknown, particularly from a forensic autopsy perspective. The present study aimed to investigate the neurological, cardiac, and pulmonary findings for a total of 388 SUDEP decedents, encompassing three cases from our forensic center during 2011–2020 and 385 literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…SUDEP refers to an unexpected, non-traumatic death in children and adults with epilepsy, where postmortem examination does not reveal any anatomical or toxicological cause of death, including drowning ( 12 , 13 ). Among the most important risk factors for SUDEP are uncontrolled or frequent GTCSs, the duration of epilepsy, prone position at the time of death, young age of first seizure, male sex, neurological comorbidities, polytherapy, ion channel or arrhythmia-related gene mutations, cardiac-respiratory dysfunction, intellectual disability, nocturnal seizures, and non-adherence to ASMs ( 12 , 14 ).…”
Section: Sudep In Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…SUDEP refers to an unexpected, non-traumatic death in children and adults with epilepsy, where postmortem examination does not reveal any anatomical or toxicological cause of death, including drowning ( 12 , 13 ). Among the most important risk factors for SUDEP are uncontrolled or frequent GTCSs, the duration of epilepsy, prone position at the time of death, young age of first seizure, male sex, neurological comorbidities, polytherapy, ion channel or arrhythmia-related gene mutations, cardiac-respiratory dysfunction, intellectual disability, nocturnal seizures, and non-adherence to ASMs ( 12 , 14 ).…”
Section: Sudep In Epilepsymentioning
confidence: 99%
“…All the SUDEP cases died at an early age (generally 10–40 years), particularly, patients with intellectual impairment, refractory epilepsy, and poorly controlled epilepsy with a high frequency of GTCS and nocturnal seizures. Studies have suggested a slight male predominance, with the male-to-female ratio being 229:159 ( 13 , 22 ).…”
Section: Sudep In Epilepsymentioning
confidence: 99%
“…Con los avances en la biología molecular se han identificado genes que codifican para canales iónicos que se coexpresan en el corazón y en el cerebro, lo que podría indicar una susceptibilidad genética común a algunos tipos de arritmias, la epilepsia y SUDEP 17,25,26 23 . Recientemente se valora como fundamental el papel de la apnea central postictial en la SUDEP 20,27 , producida por disfunción autonómica mediada por neurotransmisores en respuesta a la hipoxia que se produce durante la convulsión; la cual se está proponiendo incluso como un biomarcador para SUDEP 27 .…”
Section: Abordaje Genéticounclassified